Murder Ballads: Crime and Society in Victorian Literature - De Marinis Mezzapesa, Dalila (Journal of Artistic Creation and Literary Research, 2025)
The Victorian age is a period known not only for its rich literary tradition, but also for the high number of crimes, specifically homicides, registered in England in those years. As well as in real life, crime was one of the main issues in poetic and fictional writings. The aim of this paper is to analyse the ways in which the theme of murder in literature reflects moral changes in Victorian society, and to what extent this extreme criminal act represents a response to stifling restrictions imposed in that period. First, I will provide a broad view of the panorama in which those crimes took place and try to establish the introduction of this theme in literature with the social background of Victorian culture. I will then explore the psychological aspect of criminals as described in the dramatic monologue Porphyria’s Lover by Robert Browning, in the novel Tess of the D’Urbervilles by Thomas Hardy, and in the poem The Ballad of Reading Gaol by Oscar Wilde. The three literary works will be approached individually in each of the sections of this essay, in order to demonstrate the influence of the social background of the era upon the distorted psychology of the characters of these works